Knowledge in the Making: Cultural Memory and English Teaching. Issue 1 (2nd January 2021) - Diamond, Fleur; Bulfin, Scott
ABSTRACT: The growing interest in the history of curriculum and pedagogy in subject English might be seen as a response to educational reforms that are replacing earlier, progressive understandings of subject English with narrowly technical understandings of teacher professional knowledge and practice. This essay emerges out of an intergenerational, dialogic inquiry with late career and retired English teachers in Victoria, Australia. The study, called 'The cultural memory of English teaching', generated a range of personal-professional narratives of teaching English from the 1970s onwards. Key to their recollections was their relative professional autonomy with respect to curriculum making and text selection. This article focuses on two retired English teachers and how curriculum making was central to their efforts to use and develop their professional knowledge. We argue that a cultural memory of English teaching is an increasingly valuable resource for understanding teacher professional knowledge and for evaluating current standards-based imperatives.